The plague (of servitude) on the weak Indian. Demographic collapse of Mexico in medical-philosophical opinions of clerical factions (XVIth century) - Varella, Alexandre C. (Revista de História, 2022)
In a peculiar natural philosophy and medical knowledge of clerical expression and diffusion, plagues and deaths were linked to the regime of forced labor and the miserable life condition of a delicate and weakened Indian. If this physical condition arose from the circumstances of foreign domination, there were also thoughts about an ancestral fragile nature. Motolinia’s allegory of the ten plagues of New Spain, a philosophical treatise of Las Casas, and the Mexican academic environment, are literary and conceptual bases of the opinions of the third council, the Consejo de Indias and the chronicle of Mendieta. I conclude with some indigenous responses to their portrayed fatal weakness. In the field of the history of ideas and knowledge, I reassess the fall of the Indian from authors such as Pagden and Cañizares Esguerra, and review the narrative of the defenseless Amerindian in face of the colonial and biological conquest.